Magnetismo e propriedades estruturais de nanopartículas magnéticas obtidas por processos químicos. - Loyola, Gustavo Viali (2015)
In this work, we proposed to synthesize, stabilize and characterize structural and magnetically Fe-based nanoparticles, produced by methods of chemical reduction and precipitation. In both cases, we used the following experimental techniques: 57Fe Mössbauer spectroscopy, X-ray diffraction, Scanning and Transmission Electron Microscopies and DC and AC magnetization measurements with an Evercool-II Physical Properties Measurement System Quantum Design setup. Two types of nanoparticles were prepared using two routes. In the route-A (Nanoparticles prepared by Chemical Reduction) we performed, at room temperature, reductionhydrolysis of the FeCl3 in deionized water, using varying amounts of glycerol as controlling agent for Fe3+ ions concentration, along with the NaBH4 reducer. We investigated the effects of using different amounts of glycerol in the synthesis and drying processes of the samples on the stabilization of -Fe phase. As a result, we got Fe magnetic nanoparticles with body-centered cubic structure (a-Fe) encapsulated by amorphous-like surfaces, with a composition close to Fe2B (a-Fe2B), in which we referred as -Fe/a-Fe2B. We noted the increase in the concentration - Fe phase ( ) as a function of increasing the amount of glycerol ( ) used in the synthesis, when the samples are prepared under a vacuum and and dried at 333 K. While for wet samples we observed that the materials are sensitive to oxidation process, the vacuum dried samples were stable as shown by Mössbauer spectroscopy measurements carried out 12 months after the synthesis. For the quantities of 2, 3 and 4 ml glycerol, we produced magnetic nanoparticles of -Fe/a-Fe2B without the presence of iron oxides. In addition, we observed changes in the sample geometry of the nanoparticles. Using 4 ml of glycerol, we particularly produced nanosheets of -Fe/a-Fe2B and using 5 ml, we obtained nanoparticles of -Fe/a-Fe2B and -Fe2O3 with irregular spherical form. Due to these characteristics, this synthetic process has great potential for application in other systems with the objective of control the morphology of the nanomaterials obtained. In the route-B (Nanoparticles prepared by Chemical Precipitation) we produced nanocomposites of Fe2P dispersed in a porous carbon matrix through chemical precipitation method. In the production of the nanocomposite using activated carbon (prepared by chemical activation with H3PO4), the impregnation with Fe3+ salts in aqueous medium and subsequent heat treatments under N2 flow led to the formation of non-stoichiometric hexagonal phase Fe2-XP and the orthorhombic phase Fe-P with a ratio of 4:1. Low temperature Mössbauer spectra revealed that a large fraction (c.a 28 %) of the material is in the paramagnetic state, suggesting that part of the nonstoichiometric Fe2-XP phase is composed of very small particles. We also observed a metamagnetic phase transition around 150 K, associated with the nanoparticles of the Fe2-XP phase, with ordering temperature well below that of the Fe2P compound (~ 230 K) and being dependent on the frequency and applied AC and DC external field. Furthermore, the nanoparticles of the Fe2-XP have a hard-like magnetic character at low temperatures, with coercive field . Considering these interesting magnetic and hyperfine properties and high surface area activated carbon matrix, which does not is greatly reduced after impregnation with compounds containing Fe, we may indicate promising technological applications for the produced nanocomposite.